Problem Gambling - Barriers to Help-seeking Behaviours (Final Report) - Bellringer, M; Pulford, J; Abbott, M; DeSouza, R; Clarke, D (Auckland University of Technology (AUT), 2008)
Background: In New Zealand, as elsewhere, only a small proportion of problem gamblers seek formal help for their gambling problems. In particular, Pacific peoples appear to be significantly underrepresented relative to general population prevalence estimates from the 1999 national survey (Abbott & Volberg, 2000). There also appears to be male under-representation, especially in the case of new Maori clients, and an over-representation of females and Pakeha/Europeans seeking help for someone else’s gambling (Ministry of Health, 2006). Thus, increased understanding of the motivations and barriers for help-seeking behaviours is required. In March 2006, the Gambling Research Centre at Auckland University of Technology was commissioned by the Ministry of Health to conduct the research project Problem gambling - Barriers to help seeking behaviours. The aim of the project was to describe and understand barriers and enablers to help-seeking, and the experiences when seeking help, of people experiencing gambling harm and of their families/whanau.